2010
DOI: 10.1016/j.jvs.2010.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Younger women with symptomatic peripheral arterial disease are at increased risk of depressive symptoms

Abstract: Significant depressive symptoms are more common in younger women with PAD than in other gender-age groups, both at the time of diagnosis and 6 months later. To eradicate gender-based disparities in PAD, depression screening and monitoring in younger women may be an important direction for future research and intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…This finding has been previously demonstrated at diagnosis and long‐term follow‐up, specifically, younger women with PAD are known to be at a higher risk of depression than other gender age groups. 6 Depressive symptoms or “mood states” as well as a greater degree of bodily pain may be associated with substantially compromised functional status 48 as well as a poorer prognosis, 49 which ultimately has adverse effects on patients' health status. 5051 When we adjusted for depression scores, after including other relevant demographic, socio‐economic, and cardiovascular risk factors, we found further attenuation in the association between gender and health status for physical health status at baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding has been previously demonstrated at diagnosis and long‐term follow‐up, specifically, younger women with PAD are known to be at a higher risk of depression than other gender age groups. 6 Depressive symptoms or “mood states” as well as a greater degree of bodily pain may be associated with substantially compromised functional status 48 as well as a poorer prognosis, 49 which ultimately has adverse effects on patients' health status. 5051 When we adjusted for depression scores, after including other relevant demographic, socio‐economic, and cardiovascular risk factors, we found further attenuation in the association between gender and health status for physical health status at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…With these factors in mind, the current longitudinal study was designed to assess gender‐based differences in health status and long‐term adverse prognosis, including exploring the explanatory role of depressive symptoms for these outcomes since women are known to have worse depressive symptoms than men with PAD, and depressive symptoms have provided part of the explanation for adverse outcomes in cardiovascular disorders. 6,17 …”
Section: Introductionmentioning
confidence: 99%
“…Studies of patients with long-term depressive or anxiety disorders revealed elevated incidence of sub-clinical cardiovascular disease, as measured by a variety of parameters including plaque deposition and arterial stiffness (Seldenrijk et al, 2013), and blood pressure, glucose, body mass index (BMI), diet, and physical activity (Kronish et al, 2012). Interestingly, and relevant to sex differences often observed in the context of anxiety and depressive disorders [for which prevalence can be as twice higher in women compared to men, see Bekker and van Mens-Verhulst (2007); Kimbro et al (2012)], significant depressive symptoms are more common in younger women with peripheral arterial disease than in other gender-age groups (Smolderen et al, 2010). Also, recent meta-analysis of cardiovascular risk factors and depression in later life demonstrated relatively strong associations between depression and diabetes, cardiovascular disease and stroke (Valkanova and Ebmeier, 2013).…”
Section: Systemic Disorders Associated With Depressionmentioning
confidence: 99%
“…13-16 Prior research has also indicated that women with PAD below the age of 65 years are particularly vulnerable to experiencing depressive symptoms and that these symptoms seem to be accompanied with high rates of smoking. 17 …”
Section: Introductionmentioning
confidence: 99%